Pengembangan LKPD Berbasis Keterampilan Proses Sains dengan Pengayaan Cerita Rakyat Sambas - Dita Lindayani; Wolly Candramila; Asriah Nurdini Mardiyyaningsih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Folklore is a reflection of the life of the old community, whether in the form of fairy tales, myths, sages, or legends. In this research, the objects in the folklore of Sambas people were packaged in a worksheet as teaching materials based on science process skills. This study aimed to describe the development of a worksheet as teaching material, the results of its validation, and student questionnaire response tests on the science process skill-based living classification system sub material for high school students in class X. This type of research is descriptive of the research and development methods of the ADDIE model. The development stages used include analysis, design, development, and implementation. The research instruments used were interview sheets, validation sheets, and student response questionnaire sheets. The development of student worksheets based on science process skills-based living classification system sub material with folklore enrichment has been successfully carried out. However, the validation results are still not declared valid (CVI = 0.93), especially in conformity with basic competency, competence achievement indicators, and learning objectives, as well as providing motivation. After being revised, students responded to the results of the student worksheet by 89.06% or were in the very high category.